2006
DOI: 10.1021/jo062023n
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Platinum Group Metal-Catalyzed Carbonyl-Ene Reactions:  Carbon−Carbon Bond Formation versus Isomerization

Abstract: A comparative study of the carbonyl-ene reaction between a range of 1,1'-disubstituted or trisubstituted alkenes and ethyl trifluoropyruvate catalyzed by Lewis acid-platinum group metal complexes of the type [M{(R)-BINAP}]2+ (M = Pt, Pd, Ni; BINAP is 2,2'-bis(diphenylphosphino)-1,1'-binaphthyl) revealed subtle but significant differences in their reactivity. For instance, the palladium-based Lewis acid [Pd{(R)-BINAP}]2+ catalyzes the ene reaction between methylene cycloalkane to afford the expected alpha-hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 68 publications
1
20
0
Order By: Relevance
“…Angles closer to the ideal of 90 are seen between cis-disposed phosphorus and chlorine atoms. The bond lengths involving the Pt metal centre are similar to those in the enantiopure (R-BINAP)PtCl 2 (Doherty et al, 2006); however, deviations are observed in several of the angles. In a single unit cell, four molecules can be found ( Fig.…”
Section: Figurementioning
confidence: 56%
See 2 more Smart Citations
“…Angles closer to the ideal of 90 are seen between cis-disposed phosphorus and chlorine atoms. The bond lengths involving the Pt metal centre are similar to those in the enantiopure (R-BINAP)PtCl 2 (Doherty et al, 2006); however, deviations are observed in several of the angles. In a single unit cell, four molecules can be found ( Fig.…”
Section: Figurementioning
confidence: 56%
“…Although less common than complexes of the second-row metal Pd, atropisomers of (BINAP)PtCl 2 ( Fig. 2) have found use in catalytic reactions such as enantioselective Baeyer-Villiger oxidations of cyclic ketones with hydrogen peroxide (Strukul et al, 1997) and as precatalysts for asymmetric carbonyl-ene reactions (Doherty et al, 2006). Enantiomeric complexes of the formula L 2 PtCl 2 including (BINAP)PtCl 2 data reports have also been examined for their cytotoxic activity against cancer cell lines and their ability to bind to the human telomeric sequence folded in the G-quadruplex structure (Bombard et al, 2010).…”
Section: Structure Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…This type of ene reaction has recently been explored by other groups using Pd, Ni and Pt catalysts. [ 7 , 8 ] The importance of such reactions is derived from the ever-increasing occurrence of trifluoromethyl substituents in drugs and biologically active compounds. [ 9 , 10 ] Given that trifluoropyruvate ene reactions seemingly have a low activation barrier, and as part of our ongoing interest in hydrogen bond mediated catalysis,[ 11 ] we have investigated thioureas as H-bonding additives for organocatalytic carbonyl ene reactions and report these results here.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, it was reported that a marked effect of the counterion existed on the conversion of Lewis acid-catalyzed reaction between methylene cyclohexane and ethyl trifluoropyruvate. 26 Anhydrous Fe(BF4)2, generated from FeCl2 and AgBF4, led to higher yields than Fe(BF4)2•6H2O. Furthermore, a bidentate coordination can be postulated such that in the Cu II catalyzed carbonyl-ene reaction of ethyl glyoxylate disclosed by Evans.…”
mentioning
confidence: 99%